A rare case of intestinal obstruction caused by internal hernia through post hysterectomy peritoneal defect - Murugesan, Ravi Kumar Sabu; Ross, Kannan; Prabakar, Joyce (International Surgery Journal, 2021)
Internal hernia is a rare cause of intestinal obstruction. Nowadays acquired internal hernias are in increasing trends due to increased surgical procedures thus iatrogenic causes surpassing congenital internal hernias. Internal hernias after hysterectomy due to peritoneal defect is extremely rare. Here we present a case of 67 years old female status post hysterectomy ten years back, also a known type 2 diabetic presented to the emergency department with features suggestive of intestinal obstruction. Patient was taken up for emergency laparotomy and intra operative findings revealed small bowel loops herniating in a cavity that is formed by bladder anteriorly, caecum and sigmoid colon laterally and rectum posteriorly. Bowel loops were released. The bowel was found to be viable and the defect was closed. Bowel movements resumed on the third post-operative day. This case is presented here as it is an extremely rare case of internal hernia causing small bowel obstruction.